Anthropology and the anarchists : culture, power, and practice in militant anti-capitalist protests - Cross, Jamie J. (Universidad Nacional de Quilmes, 2003)
In recent history the metropolitan meetings of multilateral economic institutions and supra-national governing bodies have been accompanied by massive demonstrations. In Europe the actions of militant demonstrators have angered politicians, generated popular stereotypes about an anti-globalisation movement, and sparked intense debate amongst activists. This paper is an attempt to engage ethnographically with people who favour forms of confrontational protest against property and police, and identify themselves as anarchists. It is an approach that steps back from either pathologising or glorifying their actions. The paper reacts to the sanitization of gender politics and internal conflicts in many academic accounts of collective political practice. In contrast, I apply Michel Foucault and Pierre Bourdieu's theoretical tools to contemporary social movements. I emphasise that practices aimed at resisting forms of power can also be re-productive. As examples, I explore dominant representations of the developing world& that feature in activist's descriptions of protest. And I draw attention to hegemonic masculinities that operate in the midst of a demonstration. My intention is to argue that the challenge of anthropological engagement requires more than the identification of sites of struggle. The necessary political act is to bring a reflexive alertness to common sense thoughts, actions and emotions.